2013
DOI: 10.3928/01484834-20130311-02
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian, Gay, Bisexual, and Transgender Health: Fundamentals for Nursing Education

Abstract: As the health care needs of the lesbian, gay, bisexual, and transgender (LGBT) population become increasingly important, health care professionals require appropriate academic and clinical training in preparation for the increased demand for culturally competent care. Nurses are of particular interest, as they are the core direct caregivers in many health care settings. This article explores the national climate around LGBT individuals and their related health needs. Educators and administrators who work with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 27 publications
1
69
0
12
Order By: Relevance
“…Other gender‐segregated areas such as women only drop‐in centers, or other social resources intended to promote gender equality and create safe spaces, can unintentionally contribute to gender marginalization by making these spaces either implicitly or explicitly inaccessible to transgender users (Bauer et al., ; The Joint Commission, ). More gender inclusive spaces, such as those that serve LGBTQ+ interest groups, can counter that segregation and offer safety for those that do not identify or “qualify” as women or men (Lim et al., ). Nursing educators can advocate for more expressly gender‐neutral spaces in their institutions to convey cultural safety to trans‐persons and to model awareness and advocacy for their students.…”
Section: Structural and Curricular Interventions For Nurse Educatorsmentioning
confidence: 99%
“…Other gender‐segregated areas such as women only drop‐in centers, or other social resources intended to promote gender equality and create safe spaces, can unintentionally contribute to gender marginalization by making these spaces either implicitly or explicitly inaccessible to transgender users (Bauer et al., ; The Joint Commission, ). More gender inclusive spaces, such as those that serve LGBTQ+ interest groups, can counter that segregation and offer safety for those that do not identify or “qualify” as women or men (Lim et al., ). Nursing educators can advocate for more expressly gender‐neutral spaces in their institutions to convey cultural safety to trans‐persons and to model awareness and advocacy for their students.…”
Section: Structural and Curricular Interventions For Nurse Educatorsmentioning
confidence: 99%
“…Nursing organizations have called for recognition of LGBT health disparities. Lim, Brown, and Jones () noted that the codes of ethics for the American Nurses Association (ANA) and the International Council of Nurses (ICN) acknowledge the importance of valuing individuality and respecting individuals regardless of demographics and attributes, including sexual orientation. The authors observed that LGBT elders are particularly underserved given the poor health outcomes associated with aging compounded by the marginalization occurring as a sexual minority (Lim et al., ).…”
Section: Common Meanings Of Lbt‐related Terminologymentioning
confidence: 99%
“…Lim, Brown, and Jones () noted that the codes of ethics for the American Nurses Association (ANA) and the International Council of Nurses (ICN) acknowledge the importance of valuing individuality and respecting individuals regardless of demographics and attributes, including sexual orientation. The authors observed that LGBT elders are particularly underserved given the poor health outcomes associated with aging compounded by the marginalization occurring as a sexual minority (Lim et al., ). This marginalization of LGBT seniors is particularly noteworthy given that, “the proportion of same‐sex couples that include at least one senior aged 65 or older has risen from 7.5% in 2005 to nearly one in 10 (9.7%) in 2011” (Gates, , p. 1).…”
Section: Common Meanings Of Lbt‐related Terminologymentioning
confidence: 99%
“…Studies have shown that nurses are sometimes reluctant to ask about a patient's sexual orientation for fear of intruding into what is perceived to be a private matter (Lim et al, 2014). Some practitioners are concerned about appropriate terminology, or about the possibility of offending patients (Lim et al, 2013). Nurses sometimes say that there are no opportunities to enquire about sexual orientation and gender identity, yet there are numerous moments during the patient journey where disclosure may be facilitated.…”
mentioning
confidence: 99%